2016
DOI: 10.1016/j.vhri.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of the Self-Management Program for Thai Patients with Metabolic Syndrome

Abstract: The SMP provided by the health care settings is marginally cost-effective, and the persistence results support the implementation of the program to minimize the complications and economic burden of patients with MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Unfortunately, optimal diabetes care is hindered by many factors, including the lifestyle choices of patients and lack of patient education ( 5 ). Establishing and implementing self-management require the right method and support ( 6 ).…”
Section: Contextmentioning
confidence: 99%
“…Unfortunately, optimal diabetes care is hindered by many factors, including the lifestyle choices of patients and lack of patient education ( 5 ). Establishing and implementing self-management require the right method and support ( 6 ).…”
Section: Contextmentioning
confidence: 99%
“…In the one-way sensitivity analysis, we varied the cost parameters and utility weights associated with IFG by ±20%, and we varied the discount rates from 1-5%. Risk reduction of the intervention on diabetes and CVD was estimated, including distributions and 95% confidence intervals [30]. Probabilistic sensitivity analyses were conducted using Monte Carlo simulations of 1000 iterations.…”
Section: Plos Onementioning
confidence: 99%
“…Physical activity alone is not capable of achieving large weight losses, usually less than 5 kilos [12], although it does achieve notable benefits in other cardiovascular parameters such as diastolic blood pressure or triglycerides. However, research has shown that in the short term, lifestyle modification (diet and exercise) reduces obesity by obtaining cardiovascular benefits [13,14].…”
Section: Introductionmentioning
confidence: 99%